A novel long-alkyl-chained acylhydrazone-based supramolecular polymer gel for the ultrasensitive detection and separation of multianalytes. Issue 20 (8th May 2019) - Yin, Zhi-Yuan; Hu, Jing-Han; Fu, Qing-Qing; Gui, Kai; Yao, Ying
Abstract : A novel supramolecular polymer material, OGV, based on long-alkyl-chained acylhydrazone was constructed. The OGV showed an ultrasensitive response for Hg 2+ and Fe 3+ in water by forming the metallogels HgG and FeG, which showed ultrasensitive detection and separation for CN − and H2 PO4 − in water, respectively. Abstract : By rationally introducing multi-self-assembly driving forces and coordination binding sites into the same molecule, a designed functional gelator, G, was synthesized. Next, a novel supramolecular polymer material, OGV (1% DMSO), was constructed and used for the ultrasensitive detection and separation of multianalytes in gel states. Interestingly, OGV showed a fluorescent ultrasensitive response for the Hg 2+ and Fe 3+ ions in water. Moreover, by introducing these metal ions into the OGV, stable metal ion-coordinated supramolecular metallogels (HgG and FeG) were formed, which could sense CN − and H2 PO4 − in water with high selectivity and sensitivity.